Migrated intra-uterine device to infra-umbilical skin: a rare case report - Nigat Amsalu Addis; Yared Alem Sibhat; Yohannis Derbew Molla; Wasihun Nigdu Mengestu; Abebe Sinknew Seid; Michael Argaw Damite; Misganaw Abere Worku (BMC Women's Health)
Abstract Introduction IUDs are effective, reversible and safe methods of contraception. The mechanism of action of IUDs as a group is inducing endometrial atrophy, apoptosis, altering tubal motility; preventing sperm permeability, fertilization, and implantation. Complications of IUD include menstrual disturbance, pelvic pain, and increased risk of ectopic pregnancy with contraceptive failure, device expulsion, uterine perforation or transmural migration with misplacement of the device. Pregnancies and IUD migration are uncommon complications, occurring in 1 to 2 from 1,000 users. The clinical presentation of migrated IUDs depends on the final anatomic location at diagnosis. Migration can be asymptomatic and incidentally found while imaging for any other diagnosis or may have various acute clinical presentations. Case Presentation We present the case of a 38-years-old Ethiopian woman with unusual migration of IUD to the infra-umbilical skin. She had infra-umbilical skin discoloration associated with intermittent itching for two months duration. On physical examination, there was diffuse violaceous patch over the infra-umbilical skin measuring 7 centimeters on its longest dimension and visible foreign body (IUD) with tiny sinus tract formation. Visible stem of copper-containing IUD was grasped by ring forceps and removed with gentle traction without complication during or following extraction. Removal of misplaced IUD with completely non-invasive manner makes this case special in addition to the unique site of migration to the infra-umbilical skin. Conclusion and recommendation To our knowledge, this is what likely to be the first reported case of IUD migration to the infra-umbilical skin which bestows a new finding to the existing literatures. Despite rare occurrence, possible IUD complications should be included in the informed consent process before insertion. Self-examination of the strings and vigilant evaluation at regular checkup is recommended for early detection of migrated IUDs.